2007
DOI: 10.1074/jbc.m606950200
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative Stress Inhibits the Aminophospholipid Translocase Resulting in Phosphatidylserine Externalization and Macrophage Engulfment

Abstract: Macrophage recognition of apoptotic cells depends on externalization of phosphatidylserine (PS), which is normally maintained within the cytosolic leaflet of the plasma membrane by aminophospholipid translocase (APLT). APLT is sensitive to redox modifications of its -SH groups. Because activated macrophages produce reactive oxygen and nitrogen species, we hypothesized that macrophages can directly participate in apoptotic cell clearance by S-nitrosylation/oxidation and inhibition of APLT causing PS externaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 97 publications
3
68
1
Order By: Relevance
“…This implies that caspases are not involved in the clearance of phagocytic neutrophils but that an oxidant-dependent event is crucial. This is consistent with the observation of Kagan and colleagues that oxidation of PS is necessary for its externalization (16,22,30); more recently, Tyurina et al showed that in HL-60 cells exposed to nitrosative stress PS exposure was dissociated from the common apoptotic pathway (29). We have also recently reported that 24-h ascorbate-deficient neutrophils fail to undergo PS exposure and uptake by macrophages despite activation of caspases (33).…”
Section: Discussionsupporting
confidence: 92%
“…This implies that caspases are not involved in the clearance of phagocytic neutrophils but that an oxidant-dependent event is crucial. This is consistent with the observation of Kagan and colleagues that oxidation of PS is necessary for its externalization (16,22,30); more recently, Tyurina et al showed that in HL-60 cells exposed to nitrosative stress PS exposure was dissociated from the common apoptotic pathway (29). We have also recently reported that 24-h ascorbate-deficient neutrophils fail to undergo PS exposure and uptake by macrophages despite activation of caspases (33).…”
Section: Discussionsupporting
confidence: 92%
“…The first is activated microglia with upregulated microglial receptors and opsonins like MFGE8, which can recognize a stressed neuron and tag it for engulfment. The second is PS exposure on the neuronal cell surface, which can occur as a result of oxidative stress, an increase in calcium levels, or adenosine triphosphate depletion, among other possible mechanisms 29, 30, 31. PS exposure is not itself toxic to neurons, but rather marks the neuron for selective removal by microglia.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of NBD-PS internalized was determined as the percentile of dithionite-resistant NBD-PS fluorescence from the total NBD-PS fluorescence as described earlier. 26 …”
Section: Measurement Of Transbilayer Movement Of Psmentioning
confidence: 99%